Familial Hypercholesterolaemia: molecular and functional study of LDLR mutations - Pinto Pereira, Andreia Sofia (2017)
Cardiovascular disease (CVD) remains the most common cause of death globally. Dyslipidaemia is one of the most important risk factors that leads to CVD. It can be due to a monogenic condition or to polygenic/environmental causes as diabetes, obesity, tobacco use, excess of alcohol or reduced physical activity. The identification of the individuals at risk and the distinction of these two types of dyslipidaemia is important for a correct cardiovascular risk assessment, counselling, and treatment reducing, this way, cardiovascular mortality. Familial hypercholesterolaemia (FH) is an autosomal dominant disorder of cholesterol metabolism. Most commonly, FH results from inherited defects in the Low-Density Lipoprotein Receptor Gene (LDLR) leading to increased levels of circulating LDL cholesterol and lipid accumulation in arteries and tendons. Mutations in other genes as the apolipoprotein B gene (APOB) and proprotein convertase subtilisin/kexin type 9 gene (PCSK9), are also responsible for FH. The distribution pattern of apolipoprotein E gene (APOE) polymorphisms affects the affinity to lipoprotein receptors and, consequently, the clearance of dietary fat from the blood, also causing dyslipidaemia.